Pragmatics of Uncooperative and Manipulative Communication - Oswald, Steve (Neuchâtel, 2010)
This dissertation tackles the issue of uncooperative and manipulative communication from a cognitive pragmatic perspective and develops and documents the fundamental hypothesis that its success depends on whether the manipulator manages to keep the manipulative intention concealed. Specifically, manipulative communication is conceived here as a twofold process meant to i) mislead the addressee into processing limited sets of contextual information and ii) prevent her/him from processing contextual information that would be detrimental to the success of the manipulative attempt. The dissertation draws on several fields of research in the Humanities and attempts to interface findings from cognitive psychology (mainly research on cognitive biases) and argumentation theory (research on fallacies) into a consistent cognitive pragmatic account of information-processing. To this end, the so-called Contextual Selection Constraint model (CSC) is presented; this model specifies from a theoretical perspective how certain linguistic and argumentative strategies can be used to constrain the comprehension procedure so that targeted assumptions end up partaking in the derivation of meaning and other unwanted assumptions turn out to be disregarded – or unprocessed altogether. These possibilities are conceived as natural potential consequences of our cognitive system’s inherent fallibility.
, PhD, Université de Neuchâtel, Institut des Sciences du Langage et de la Communication
Keywords: pragmatics; manipulation; uncooperativeness; relevance; argumentation; fallacies; biases; cognition